Dietary Protein and Energy Balance in Relation to Obesity and Co-morbidities - Drummen, Mathijs; Tischmann, Lea; Gatta-Cherifi, Blandine; Adam, Tanja; Westerterp-Plantenga, Margriet (Frontiers in Endocrinology, 2018)
1. Abstract Dietary protein is effective for body-weight management, in that it promotes satiety, energy expenditure, and changes body-composition in favor of fat-free body mass. With respect to body-weight management, the effects of diets varying in protein differ according to energy balance. During energy restriction, sustaining protein intake at the level of requirement appears to be sufficient to aid body weight loss and fat loss. An additional increase of protein intake does not induce a larger loss of body weight, but can be effective to maintain a larger amount of fat-free mass. Protein induced satiety is likely a combined expression with direct and indirect effects of elevated plasma amino acid and anorexigenic hormone concentrations, increased diet-induced thermogenesis, and ketogenic state, all feed back on the central nervous system. The decline in energy expenditure and sleeping metabolic rate as a result of body weight loss is less on a high-protein than on a medium-protein diet. In addition, higher rates of energy expenditure have been observed as acute responses to energy-balanced high-protein diets. In energy balance, high protein diets may be beneficial to prevent the development of a positive energy balance, whereas low-protein diets may facilitate this. Furthermore, high-protein, low-carbohydrate diets may be favorable for the prevention of metabolic disturbances. With respect to protein turnover, it is important to distinguish the fasted state from the fed state. A positive protein balance observed at a high-protein diet may be due to acute postprandial responses. During positive energy balance, excess energy intake alone may account for the increase in fat mass. High-protein diets seem to contribute to prevention of non-alcoholic fatty liver disease (NAFLD), and, depending on the protein source, type 2 diabetes but not to cardiovascular diseases beyond their effect on body-weight management. However, observations on the latter from different studies are inconclusive. High-protein diets do not seem to have adverse effects on these co-morbidities. In conclusion, higher protein diets may reduce overweight, obesity and NAFLD, and may reduce the risk on type 2 diabetes and cardiovascular disease risk by its effect on body-weight management.